Desain Furniture Teknik Rustic - Sari, Desnila; Natalia, Monika; Mirani, Zulfira; Partawijaya, Yan; Atmaja, Jajang (Jurnal Abdimas: Pengabdian dan Pengembangan Masyarakat, 2024)
The use of waste can be a surefire alternative to making furniture at less cost. It can be commercial ideas, and profitable business, processing wasted materials into unique furniture, without losing naturalness. The concept of rustic is utilizes natural resources. Rustic style can be interpreted as a style in architectural and interior design the impression of natural and beautiful. In processing finishing it is done imperfectly it must remain in a rough texture. Finishing is done only to protect weather materials and termites. The application of independent community science and technology about rustic technique furniture design has been carried out at Panti Sasuhan Khusus Anak Mentawai, Purus 4 Padang, on Sunday, August 27, 2023. This activity was carried out by socializing about waste materials to how to make rustic technique furniture, by discussion and question and answer. The success of this activity can be seen from the enthusiasm of participants in discussions and questions and answers as well as their interest in trying to make their own later. This activity, it is expected to increase the insight, knowledge and skills of orphanage children to be able to become independent entrepreneurs by utilizing unused natural materials into beautiful furniture that is selling.